Pelatihan Sablon Digital untuk Peningkatan Keterampilan Wirausaha pada Peserta GHS - Robby Mukhtar (Lembaga Pengembangan Kinerja Dosen, 2025)
Digital screen printing training is a strategic step to address the need for enhancing entrepreneurial skills in an increasingly competitive digital era. This program is conducted intensively, with a primary focus on providing knowledge and practical skills in digital screen printing techniques. The training is designed to include brief theoretical sessions, in-depth hands-on practice, and intensive mentoring to ensure participants can produce high-quality screen printing products ready for the market.The participants consist of 25 individuals from Gentala Hospitality School who aim to build or develop creative businesses in the field of digital screen printing. The results of the training show a significant improvement in mastering digital screen printing techniques, skills in using design software, and the ability to create marketable products. This training is expected to help participants start professional digital screen printing businesses and support the growth of the creative economy in Jambi.